Draft 11th Five Year Plan (2007-12) and Draft Annual Plan (2007-2008), Part I (Background) - Planning Commission (Planning Commission, 2007)
One of the seven sisters of the North Eastern Region, Tripura has diverse range of topography, people, flora and fauna. It has geographical area of 10,491.69 sq.km. and 31,91,168 (as per 2001 Census) population. It is flanked by Bangladesh on three sides with an international border length of 856 km. along with a small corridor with Assam and Mizoram on the North Eastern side. Tripura has undulating topography, with 60 per cent of the geographical area under forest coverage, the state is rich in bio-diversity. Six hill ranges, namely Jampui, Sakhangtang, Longtharai, Atharamura, Baramura, Debtamura and Kalajhari run on north south direction in the State.
Planning (P&C) Department Government of Tripura